Cyclical behavior of genotype frequencies in a two-locus population under fluctuating haploid selection. - Kirzhner, V M (1994)
Numerical iterations have shown that periodic haploid two-locus selection with nonoverlapping generations can produce large-scale cyclical behavior with a period differing significantly from the environmental period. Among other types, we observed slowly damping oscillations with very long periods, stable T-cycles with a length containing several environmental periods, and chaotic-like dynamics. Possible biological implications are discussed.